Overexpression of miR‐98 attenuates neuropathic pain development via targeting STAT3 in CCI rat models. Issue 5 (28th November 2018) - Zhong, Liang; Fu, Kui; Xiao, Weimin; Wang, Fang; Shen, Lu‐Lu
Abstract: MicroRNA (miRNA) are significant regulators of neuropathic pain development and neuroinflammation can contribute a lot to the progression of neuropathic pain. Recently, miR‐98 has been reported to be involved in various diseases. However, little is known about the role of miR‐98 in neuropathic pain development and neuroinflammation. Therefore, our study was aimed to investigate the function of miR‐98 in neuropathic pain via establishing a rat model using chronic constriction injury (CCI) of the sciatic nerve. Here, we observed that miR‐98 was downregulated in CCI rat models. Overexpression of miR‐9 was able to inhibit neuropathic pain progression. Recently, STAT3 has been reported to serve a key role in various processes, including inflammation. Interestingly, our study indicated that STAT3 was dramatically upregulated and activated in CCI rats. By using informatics analysis, STAT3 was predicted as a direct target of miR‐98 and the direct correlation was confirmed. Then, miR‐98 was overexpressed in CCI rats and it was found that miR‐98 was able to repress neuropathic pain development via inhibiting the neuroinflammation. As displayed, interleukin 6 (IL‐6), IL‐1β, and tumor necrosis factor‐α (TNF‐α) expression was obviously induced in CCI rats, while miR‐98 reduced their protein levels. Finally, we found that overexpression of STAT3 reversed the inhibitory effect of miR‐98 on neuropathic pain development. Taken these together, we reported that overexpression of miR‐98 attenuated neuropathic pain development via targeting STAT3 in CCI rat models. Abstract : Our study indicated a significant role of miR‐98/STAT3 axis in neuropathic pain. We reported that miR‐98 was able to alleviate neuropathic pain development via targeting STAT3.